Eraserhead [videorecording (DVD)] - Lynch, David, 1946-; Lynch, David, 1946-; Nance, Jack; Stewart, Charlotte, 1941-; Joseph, Allen (Criterion collection, 2014)
An obscure man with a vertical head of hair is living with his spaced-out girlfriend and their fetus-like child. By the end of the film, Henry is decapitated and processed into erasers in this bizarre horror film which closely approaches a nightmare.